Instant OSGi starter : the essential guide to modular development with OSGi - Edstrom, Johan (Packt Pub., 2013)
Using a practical approach with explanation where needed, the book will take an in depth look at what OSGi is and what it offers to Java programmers and development standards. ""OSGi Starter"" is intended for the senior Java programmer whom will be joining OSGi based projects, or for Architects looking to broaden their exposure to OSGi as a beneficial framework and runtime software system.